Addressing and anticipating food safety challenges: microbiology and policy frameworks for Shiga toxin-producing Escherichia coli (STEC) and Salmonella - Unruh, Daniel Alan (Kansas State University, 2018)
Food safety is a public health issue that demands coordinated scientific and policy solutions. Despite advancements in interventions and surveillance, Shiga toxin-producing Escherichia coli (STEC) and Salmonella spp. continue to cause outbreaks in a wide variety of food products. In light of these public health urgencies, both microbiological and policy frameworks are needed to address and anticipate future food safety challenges related to these pathogens. Laboratory-based techniques are used to address (1) whether common processing stresses change the susceptibility of STEC and Salmonella to food-grade antimicrobials, (2) whether differences in STEC attachment to beef tissue can inform intervention strategies, and (3) the efficiency of a combined sanitizer approach to reduce Salmonella on spinach. Salmonella Montevideo, Newport, and Typhimurium, and STEC O26, O45, O103, O111, O145, and O157:H7 were subjected to salt, acid, heat, freeze-thaw, alkaline and no (control) stress, and then challenged with the antimicrobials lauric arginate, citric acid plus hydrochloric acid, peroxyacetic acid plus acetic acid and hydrogen peroxide, lactic acid plus citric acid, and lactic acid. Growth/inhibition/no-growth was determined by absorbance values. While differences (p≤0.05) were observed between some of the stressors and controls, the minimum inhibitory concentrations (MICs) observed for both STEC and Salmonella were below maximum concentrations permitted by the United States Department of Agriculture (USDA). STEC serogroups were grown in nutrient-dense or nutrient-limiting media and inoculated onto lean or adipose, pre-rigor (warm) or chilled beef tissue. Loosely and firmly attached cells were plated onto MacConkey agar at several time points. When grown in nutrient-dense media, time × sample type (buffer versus homogenized sample) and sample type × tissue type (adipose versus lean) were significant (p<0.001). For nutrient-limited cells, tissue type was a significant main effect (p=0.0134). Spinach was inoculated with 5.0 log CFU/g Salmonella, dried, and submerged in a sodium bisulfate peroxyacetic acid (SBS-PAA) wash, a chlorine wash, or water for 2 min. Samples were stored for 0, 1, 3, 5, and 10 d, and populations were enumerated. When plated on xylose-lysine-tergitol 4 (XLT-4), SBS-PAA and chlorine washes achieved significant reductions (p≤0.05). When plated on XLT-4 plus tryptic soy agar (TSA) overlay, SBS-PAA was the most effective treatment, with a reduction of 1.77 log CFU/g (p<0.0001). Recognizing that microbiology studies ought to be combined with policy frameworks (and potential food safety solutions), policy analyses were performed to (1) evaluate and make recommendations about the resilience of the U.S. food system to catastrophic events and (2) thoughtfully—and innovatively—address so-called “unknown unknowns” (or disasters) and forecast future food safety vulnerabilities. The U.S. food system and its response to an intentionally-contaminated food product are analyzed through responsibilities of public, private, and third-sector actors. To address unknown unknowns and more strategically address future food safety problems, public and private actors ought to: (a) learn from the past (i.e., the German O104 outbreak), (b) target food groups of high and/or increasing consumption, (c) assess threats primarily rooted in other critical infrastructures, (d) borrow concepts and principles from meteorological forecasting, and (e) advocate multidisciplinary thinking.
Keywords: Food safety; Food policy; Escherichia coli; Salmonella; Food microbiology; Resilience